Optimism in Male University Students with Partial Color Blindness - Tsabita Huwaida; Diana Rahmasari (Universitas Negeri Surabaya, 2023)
Partial color blindness is a condition that hinders the recognition and categorization of specific colors, resulting in discomfort and a series of disparities for those affected. Opportunities to pursue aspirations are often denied due to regulations in professions such as nursing, engineering, and public service that impose binding rules regarding partial color blindness, leading to the curtailment of rights for many individuals with this condition. Consequently, it can have profound psychological implications for individuals with partial color blindness. This qualitative research, employing a case study approach, aims to uncover the factors that contribute to optimism among male university students with partial color blindness. Through semi-structured interviews with three male participants and employing thematic analysis, the study successfully identifies three key factors that influence the formation of optimism: (1) social support, (2) confidence, and (3) self-esteem. These factors empower participants to face the psychological challenges posed by partial color blindness and foster a sense of optimism